Teori Pembelajaran Berbasis Otak Dalam Perspektif Pendidikan Islam - Yusuf, Muhamad Hani (Universitas Yudharta Pasuruan, 2023)
The brain is a unique thing that functions as the centre of thought and also the birth of ideas that humans have. The brain is a discussion that must be dissected, of course, so that the brain can develop properly. So that education will not be separated from the role of the brain that each student has. This research uses library research, which uses the initial steps of searching for data sources, analysing and providing conclusions so that researchers can find gaps in previous research. There is discussion d in this writing. Brain-based learning and the theory that underlies it, the importance of applying brain-based learning in Islamic education, using brain-based learning in Islamic education. Brain-based learning utilises the way the brain works in compiling knowledge and skills. Train brain development and students' potential in connecting the brain, mind, heart, soul and mind so that they can maximise their brain abilities related to the spiritual brain (SQ), rational brain (IQ), and emotional brain (EQ) so that participants Students can humanise humans and the ability to learn cognitively, affectively and psychometrically.